A new insight about pharmaceutical dosage forms for benzathine penicillin G. - K. G. HOLANDA E SILVA; F. H. XAVIER-JúNIOR; I. E.G. FARIAS; J. A. CALDAS NETO; A. K.A.S. SILVA; T. NAKASHIMA-JúNIOR; I. B. ARAúJO; A. G. OLIVEIRA; A. C. MEDEIROS; E. S. TABOSA DO EGITO (São Paulo State University (UNESP), 2006)
In this work, a micellar system of benzathine penicillin G (BPG) in sodium deoxycholate (NaDC) was developed and evaluated physicochemically. The solubility profile of the drug in water and buffer solutions at various pH was determined, as well as its n-octanol/water partition coefficient. The Critical Micellar Concentration of NaDC and its ability to incorporate BPG were also assessed. The study was carried out at low and high ionic strength which was adjusted by the addition of sodium chloride. The results demonstrated the ability of the micellar system to incorporate BPG, as well as to increase its apparent solubility in water. The enhancement of the solubility of BPG by the presence of NaDC micelles could be analyzed quantitatively within the framework of the pseudo-phase model. Concentration analysis showed that the micellar system could attain up to 90% incorporation of BPG. The incorporated drug is expected to exhibit improved stability, since the antibiotic enclosed in the hydrophobic core of micelles is rather shielded from the aqueous external environment.